Atom‐Specific Mutagenesis Reveals Structural and Catalytic Roles for an Active‐Site Adenosine and Hydrated Mg2+ in Pistol Ribozymes. (15th November 2017) - Neuner, Sandro; Falschlunger, Christoph; Fuchs, Elisabeth; Himmelstoss, Maximilian; Ren, Aiming; Patel, Dinshaw J.; Micura, Ronald
Abstract: The pistol RNA motif represents a new class of self‐cleaving ribozymes of yet unknown biological function. Our recent crystal structure of a pre‐catalytic state of this RNA shows guanosine G40 and adenosine A32 close to the G53–U54 cleavage site. While the N1 of G40 is within 3.4 Å of the modeled G53 2′‐OH group that attacks the scissile phosphate, thus suggesting a direct role in general acid–base catalysis, the function of A32 is less clear. We present evidence from atom‐specific mutagenesis that neither the N1 nor N3 base positions of A32 are involved in catalysis. By contrast, the ribose 2′‐OH of A32 seems crucial for the proper positioning of G40 through a H‐bond network that involves G42 as a bridging unit between A32 and G40. We also found that disruption of the inner‐sphere coordination of the active‐site Mg 2+ cation to N7 of G33 makes the ribozyme drastically slower. A mechanistic proposal is suggested, with A32 playing a structural role and hydrated Mg 2+ playing a catalytic role in cleavage.